2018
DOI: 10.3892/mmr.2018.9420
|View full text |Cite
|
Sign up to set email alerts
|

Alpinetin inhibits proliferation and migration of ovarian cancer cells via suppression of STAT3 signaling

Abstract: Natural bioactive components are increasingly being applied in cancer research. Alpinetin is a type of natural flavonoid primarily derived from Alpinia katsumadai Hayata, which exhibits anti‑bacterial and anti‑inflammatory properties. Therefore, it may possess anticancer potential and be employed therapeutically for different diseases. The aim of the present study was to investigate the anticancer effects of alpinetin on the SKOV3 ovarian cancer cell line. The effect of alpinetin treatment on SKOV3 cell prolif… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
24
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 30 publications
(25 citation statements)
references
References 21 publications
1
24
0
Order By: Relevance
“…It is considered as the primary active ingredient of Zingiberaceae ( Alpinia katsumadai Hayata) [2]. Modern pharmacological research shows a series of pharmacological activities that are involved in alpinetin, including anti-inflammatory [3,4,5,6], anti-cancer [7,8,9,10], anti-oxidant effects [11]. Alpinetin was found to improve the sensitivity of drug-resistant lung cancer cells to cis-diammined dichloridoplatium [10], which may be used as a potential drug for combination therapy.…”
Section: Introductionmentioning
confidence: 99%
“…It is considered as the primary active ingredient of Zingiberaceae ( Alpinia katsumadai Hayata) [2]. Modern pharmacological research shows a series of pharmacological activities that are involved in alpinetin, including anti-inflammatory [3,4,5,6], anti-cancer [7,8,9,10], anti-oxidant effects [11]. Alpinetin was found to improve the sensitivity of drug-resistant lung cancer cells to cis-diammined dichloridoplatium [10], which may be used as a potential drug for combination therapy.…”
Section: Introductionmentioning
confidence: 99%
“…The generation of mtSOs and reduced expression of anti-apoptotic Bcl-2 family proteins by ILL resulted in the loss of MMP ( Figure 3 C). Several previous reports suggested that STAT3 participates in the regulation of the anti-apoptotic Bcl-2 family proteins in human OC cells [ 35 , 36 ]. In the present study, ILL treatment dramatically reduced the expression and phosphorylation of STAT3, as well as the expression levels of surviving, in a time- and dose-dependent manner, while ILL decreased expression of JAK2 only in SKOV-3 cells and inhibited phosphorylation of JAK2 at the highest dose ( Figure 4 A,B).…”
Section: Discussionmentioning
confidence: 99%
“…Therapeutic strategies focused on specific cancer metabolism linked to the Warburg effect are currently under extensive consideration [174,175]. To this end, naturally occurring bioactive compounds of plants demonstrate clinically relevant beneficial effects against cancer development and progression [223][224][225][226][227][228][229][230]. The combination use of phytochemicals and chemotherapeutical drugs may represent an optimal modality for anticancer therapy [231].…”
Section: Conclusion and Expert Recommendationsmentioning
confidence: 99%